Is Inducible Nitric Oxide Synthase (iNOS) Promising as a New Target Against Pulmonary Hypertension? - Piotr Ryszkiewicz; Eberhard Schlicker; Barbara Malinowska (Antioxidants)
Pulmonary hypertension (PH) is a progressive disease characterized by elevated blood pressure in the pulmonary arteries, associated also with inflammation and oxidative stress. Inducible nitric oxide synthase (iNOS) is one of the key mediators of inflammation and immune system activation. Although preclinical studies mostly suggest a detrimental role of iNOS overactivation in PH, there is a lack of exhaustive analyses and summaries. Therefore, this literature overview aims to fill this gap. The involvement of iNOS in the pathogenesis of the four main clinical groups of PH is discussed to assess whether targeting iNOS could be a promising way to treat PH. iNOS expression patterns in the organs primarily affected by PH are analyzed both in animals and in humans. Consequently, the effectiveness of pharmacological iNOS inhibition and/or iNOS gene deletion is discussed and compared, also with reference to the activity of constitutive NOS isoforms, particularly endothelial NOS (eNOS). Overall, our overview suggests that selective iNOS inhibitors could be considered as a novel treatment strategy for PH, as decreases in right ventricular and pulmonary artery pressure, the alleviation of ventricular hypertrophy, and improvements of pulmonary and cardiac function were observed, among others. Nevertheless, further research efforts in this area are needed.